SOCIO-ECONOMIC POTENTIAL OF REGIONS AND DIRECTIONS FOR THE EFFICIENT USE OF NATURAL RESOURCES - Murtazayev Isabek Bazarbayevich (Innovate Conferences, 2025)
This article provides a comprehensive analysis of the Zarafshan region’s location, natural-geographical conditions, mineral raw material resources, demographic structure, and economic potential. The shares of Samarkand, Navoi, and Bukhara regions in the national gross domestic product, as well as their roles in industry, agriculture, transport-communication networks, and service sectors, are presented based on statistical data. The mineral resource base, strategic transport opportunities, and demographic potential are assessed as the key factors determining the role of the Zarafshan region in the national economy and its prospects for development.
Keywords: industrial potential, agriculture, demographic potential, environmental problems, transport infrastructure, investment, oil and gas industry.